PROFIL DEMOGRAFI PESERTA PELATIHAN JARAK JAUH ONLINE BALAI DIKLAT KEAGAMAAN JAKARTA - Syaddad Suryadi (Balai Diklat Keagamaan Jakarta, 2021)
Abstract This study aims to describe demographic aspects of the Distance Training (PJJ) participants at the Balai DIklat Keagamaan Jakarta (Jakarta Religious Education and Training Office). The demographic aspect includes geography, age, gender, employment status, education level, employment rank, employment position, and work. For this purpose, ex post facto research has been carried out to analyze participants 2018 until 2021 data base downloaded from Learning Management System (LMS). The research was conducted in October and September. Descriptive statistic was used to see the demographic trends. The results showed that there were trends in the demographic aspect of the participants. Firstly, the number of PJJ participants has continued to increase in the last four years. Secondly, the highest number of participants came from DKI, Banten and West Kalimantan respectively. Thirdly participants age was mostly in the range of 40-50 years. Fourthly, PJJ participants were far more female than male. Fifth participants with an undergraduate education level were very dominant. Sixth, the number of PNS participants is much higher than non-PNS. Seventh, the most participants positions are orderly teachers, religion counselor, education supervisors, madrasah heads, penghulu and administrative officials. Eighth, the most PNS PJJ participants are group of III/c to III/d level. Nineth PJJ participants came from all offices but the most were from madrasahs. Researcher recommends conducting supporting research to explain the implied motives; and to consider findings to formulate policies on PJJ improvement program in the following year. Abstrak Penelitian ini bertujuan untuk mendeskripsikan karakter demografi peserta Pelatihan Jarak Jauh (PJJ) di Balai Diklat Keagamaan Jakarta. Karakter demogafi yang dimaksud adalah geografi, usia, jenis kelamin, status kepegawaian, tingkat pendidikan, pangkat, jabatan, dan instansi. Untuk tujuan tersebut telah dilakukan penelitian ex post facto dengan sumber data base peserta yang ada dalam Learning Management System (LMS) tahun 2018 sampai 2021. Penelitian dilakukan bulan Oktober dan September. Data yang diperoleh diolah menggunakan statistik deskriptif sehingga terlihat kecenderungan-kecenderungan karakter demografi. Hasil penelitian menunjukkan bahwa terdapat kecenderungan-kecenderungan pada aspek demografi peserta. Pertama jumlah peserta PJJ terus meningkat pada empat tahun terakhir. Kedua jumlah peserta terbanyak secara berurutan berasal dari DKI, Bantn dan Kalbar. Ketiga usia peserta terbanyak pada rentang 40-50 tahun. Keempat peserta PJJ perempuan jauh lebih banyak dari pada laki-laki. Kelima peserta dengan tingkat pendidikan S1 sangat dominan. Keenam jumlah peserta PNS jauh lebih banyak dari pada non-PNS. Ketujuh, urutan peserta terbanyak dari jabatan guru, penyuluh, pengawas, kepala madrasah, penghulu dan pejabat administratif. Kedelapan, golongan PNS terbanyak yang engikuti PJJ bergolongan III/c sampai III/d. Kesembilan asal peserta PJJ berasal dari seluruh instansi dan peserta terbanyak dari madrasah. Hasil penelitian baru menghasilkan data kuantitatif sehingga direkomendasikan untuk melakukan penelitian pendukung agar dapat menjelaskan motif-motif yang tersirat. Meskipun begitu data-data kuantitatif sudah ada yang dapat digunakan sebagai landasan untuk pertimbangan membuat kebijakan perbaikan penyelenggarakan PJJ di tahun depan.